2012
DOI: 10.1111/j.1467-9892.2012.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐order integer valued AR processes with zero inflated poisson innovations

Abstract: The first‐order nonnegative integer valued autoregressive process has been applied to model the counts of events in consecutive points of time. It is known that, if the innovations are assumed to follow a Poisson distribution then the marginal model is also Poisson. This model may however not be suitable for overdispersed count data. One frequent manifestation of overdispersion is that the incidence of zero counts is greater than expected from a Poisson model. In this paper, we introduce a new stationary first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 23 publications
(21 reference statements)
1
100
0
Order By: Relevance
“…For example, a Poisson distribution is usually used to model counts and that type of data is common in JABA reports. Alternative analytic methods based on the Poisson distribution are under development (Jazi, Jones & Lai, 2012) and represent an alternative choice for future analysis of these types of data.…”
Section: Itsa Limitationsmentioning
confidence: 99%
“…For example, a Poisson distribution is usually used to model counts and that type of data is common in JABA reports. Alternative analytic methods based on the Poisson distribution are under development (Jazi, Jones & Lai, 2012) and represent an alternative choice for future analysis of these types of data.…”
Section: Itsa Limitationsmentioning
confidence: 99%
“…An approach for dealing with an excess of zeros was considered by Jazi et al (). They introduced an INAR(1) process with zero‐inflated Poisson innovations and showed that the marginal distribution of the process is also zero‐inflated.…”
Section: Introductionmentioning
confidence: 99%
“…The data were used by Jazi et al. () in the context of integer‐valued time series modelling with zero‐inflated Poisson innovation. The data series has a large proportion of zeros (40.47%), with all the observations lying between 0 and 6, except for two observations, which were 8 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration, we analyse practical data, namely skin lesion data given in Jazi et al. () to see the effectiveness of our proposed process over the PINAR(1) process.…”
Section: Introductionmentioning
confidence: 99%